DIGITAL FINANCIAL LITERACY AND FINANCIAL BEHAVIOR: THE MEDIATING ROLE OF SOCIAL MEDIA - Eshpulatova Muazzam Barnoyevna, (TADQIQOTLAR, 2025)
Abstract This  thesis  examines  the  relationship  between  digital  financial  literacy  and financial behavior, with a particular focus on the mediating role of social media. In the context of rapid digitalization, financial decision-making processes are increasingly shaped by online information environments, especially social media platforms. While social media provides broad access to financial knowledge, it also exposes individuals to unverified, biased, and sometimes misleading content. This study argues that social media does not influence financial behavior directly; rather, its impact is mediated through the level of digital financial literacy. Using a theoretical framework grounded in  human  capital  theory  and  behavioral  economics,  the  thesis  highlights  the institutional and educational mechanisms required to transform social media into an effective tool for improving financial behavior and economic stability.